Academic Performance and College Dropout: Using Longitudinal Expectations Data to Estimate a Learning Model - Stinebrickner, Ralph; Stinebrickner, Todd (Journal of Labor Economics, 2014)
We estimate a dynamic learning model of college dropout, taking advantage of unique expectations data to greatly reduce our reliance on standard assumptions. Our simulations show that 45% of dropout in the first 2 years of college can be attributed to what students learn about their academic performance, with this type of learning playing a smaller role later in college. Poorly performing students tend to leave because staying is not worthwhile rather than because they are at risk of failing out of school. Poor performance substantially decreases the enjoyability of school and substantially influences beliefs about postcollege earnings.